Evasión fiscal a las alcabalas e incentivos para el pago del impuesto predial en Ecuador: análisis de teoría de juegos. - Herrera Granizo, Adriana Yamilet (2022)
This research proposes a game theory model that analyzes the interaction between two agents, the State, and the taxpayer, using a realistic probability (frequency) approach for the evasion control strategy. Starting from the Von Neumann-Morgenstern model, we study a possible measure to prevent tax evasion to the alcabalas that the best decision is to pay. It also proposed an "honesty award" for taxpayers who declare the property tax using the Balance of Nash. This methodology states space for further model development, leading to self-identification by tax evaders and honest citizens.